Authenticity of documents, data security, and data privacy law in the Philippines: towards the future adoption of a legal management information system in the Environmental Management Bureau through scenario building - Pammit, Janice R. (University of the Philippines Diliman, 2023)
The proliferation of technology and innovation in the legal field is one of the attempts to modernize the processes and systems which are in place. According to the Strategic Plan for Judicial Innovations 2022-2027 of the Philippine Supreme Court, it is essential to establish new frameworks and adopt new approaches to achieve the longtime aspiration of delivering responsive and real- time justice to all.